(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
This study was to investigate the removal of Remazol Yellow dye from aqueous solutions by adsorption on activated charcoal prepared by chemical activation of saw dust. The dye removal was 85% which was increased to 94% with the addition of 1.0 g of NaCl electrolyte for 50 mL dye solution. The data were well fitted in Langmuir isotherm. The interactions were evaluated with respect to both pseudo-first-order and pseudo-second-order reaction kinetics. The adsorption process was found to follow the pseudo-second-order model. To optimize the operating conditions, the effect of pH, temperature, adsorbent dosage, and initial dye concentration and initial volume of dye solutions were investigated. The obtained results indicated that the utilization of activated charcoal produced from saw dust played an important role in the removal of Remazol Yellow(RY) dye from aqueous solutions. In addition, saw dust was low cost and easily available material. It can be an alternative adsorbent precursor for more expensive adsorbents used for RY removal. Bangladesh J. Sci. Ind. Res. 50(4), 285-292, 2015